Anti-aging mechanism and effect of treatment with raw and wine-steamed Polygonatum sibiricum on D-galactose-induced aging in mice by inhibiting oxidative stress and modulating gut microbiota - Zhong, Ruixue; Shen, Ling; Fan, Yilin; Luo, Qiaomei; Hong, Ran; Sun, Xiaoli; Zhou, Xia; Wan, Jun (Frontiers in Pharmacology, 2024)
Background: Polygonatum sibiricum (PS) is a traditional Chinese medicine (TCM) first recorded in Mingyi Bielu. The book documents that PS can nourish five internal organs, be taken for a long time, relax the body and prolong lifespan. Presently, PS is widely used in TCM to prevent premature graying of hair. Based on TCM theory and clinical trials, the wine steaming processed product from PS provides a better effect. However, no published study has elucidated the anti-aging mechanism.Purpose: The study aim was to investigate the anti-aging mechanism of PS and its wine steaming processed product in mice, specifically focusing on the effect of D-galactose (D-gal) surrounding the intestinal flora and the Kelch-like ECH-associated protein 1-nuclear factor erythroid 2-related factor 2-antioxidant response elements (Keap1/Nrf2/ARE) pathway.The chemical components in Raw PS (RPS) and WinedWine-steamed PS (WPS) were identified by ultra-performance liquid chromatography-hybrid quadrupole-Orbitrap highresolution mass spectrometry (UPLC-Q-Orbitrap HRMS). An aging model using Kunming mice was established through intraperitoneally injected D-gal. Concentrations of RPS and WPS at 5, 10, or 15 g/kg/day levels were administered intragastrically, respectively. The body weight, liver and spleen indexes, superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), and malondialdehyde (MDA) activities in serum and brain tissue were recorded. Hematoxylin and eosin (HE) stained brain tissue was histopathologically examined. The expressions of Keap1, Nrf2 and heme oxygenase 1 (HO-1) in the brain tissue at the mRNA and protein levels were respectively detected by reverse transcription-polymerase chain reaction (RT-PCR) and western blot (WB). Moreover, an Illumina Hiseq platform was used for 16S ribosomal RNA (16S rRNA) high-throughput sequencing to evaluate the proportions of intestinal flora in aging mice.The results demonstrated that PS and its WPS had a positive effect in relieving oxidative stress in aging mice. WPS outperformed RPS, which might be related to the activation of the Keap1/Nrf2/ARE pathway and regulation of intestinal flora.